Multi Criteria Framework for Sustainable Agriculture Infrastructure : A Techno-economic and Environmental Assessment of Renewable Powered Irrigation System in Pakistan - Sheharyar (321098); Dr. Muhamad Yousif (USPCAS-E, NUST,Islamabad, 2023)
TH-495
Keywords: MS Thesis; MS-EEP Thesis